Fatal haemonchosis (H. contortus) in Garole sheep at coastal region in Bangladesh - Paul, Torun Kumar; Rahman, Md Khalilur; Haider, Md Shahriar; Saha, Shib Shankar (Research in Agriculture Livestock and Fisheries, 2020)
Among gastro intestinal nematodes, Haemonchus contortus is one of the most pathogenic parasites of small ruminant in many countries of the world, including Bangladesh. Garole breed of sheep are adapted to the hot coastal regions in Bangladesh, and able to graze on marshy land. Sheep farm of Grameen Jano Unnayan Sangstha (GJUS), Bhola, a coastal region of Bangladesh faced sudden lamb mortality during the period of May, 2019 to August, 2019. Routine investigation was performed and data were summarized to find out the etiology, control measures and possible risk factors. During investigation both clinical and management history, physical examination and necropsy were performed. Salient case history includes: only Garole lamb with poor body condition at hot and humid climate died. Important clinical manifestation is defecation of bad odoured scanty blackish faeces. Physical examination of affected sheep revealed anemia and submandibular edema. Necropsy findings showed numerous Haemonchus sp. and frank haemorrhage in the abomasum. For control, all affected sheep were treated with anthelmintic, Nitroxynil (Nitronex®) and other supportive therapy; 4 hour after injection with Nitronex® one sick lamb was died, that might be due to anthelmintic stress, and others recovered within 3-5 days. This is the first report on haemonchosis in Garole sheep at coastal regions of Bangladesh; it will help the sheep rearers in the region to take protective measures against the fatal haemonchosis. Res. Agric., Livest. Fish.7(1): 107-112, April 2020